Pengaruh Logam Merkuri (Hg) Terhadap Pertumbuhan Seruni Rambat (Wedelia trilobata L. Hitchc) - Mukarlina, Levita Meivi Lona, Riza Linda (Universitas Tanjungpura, 2015)
Phytoremediation is a remediation method by using plants with high tolerance to improve the quality of soil contamined with heavy metals. This research aimed to find out the effect of Hg metals on the growth of the wedelia (Wedelia trilobata L. Hitch) and to find out the ability of absorbing the mercury in the leaves and roots. The research used a completely randomized design (CRD) with 5 treatments and 3 replicated, i.e. 0 ppm HgCl2, 100 ppm HgCl2, 200 ppm HgCl2, 300 ppm HgCl2 and 400 ppm HgCl2. The research finding indicated that the mercury treatment had no significant effect on the parameters of plant height, number of leaves, fresh weight and dry weight. The mercury concentration absorbed by the roots ranged from 0.1128 to 0.2997 mg/g,and by the leaves ranged from0.0221 to 0.0287 mg/g. The wedelia was tolerance and still capable of adapting to mercury at a concentration of mercury at 400 ppm.